Oliver Twist - Dickens, Charles, 1812-1870 (Lahore, Pakistan Readings, 2014)
Adventures of an orphan boy who lives in the squalid surroundings of a nineteenth-century English workhouse until he becomes involved with a gang of thieves.
Keywords: Orphans -- England--London -- Criminals